Post Partum Blues: Pentingnya Dukungan Sosial Dan Kepuasan Pernikahan Pada Ibu Primipara - Dila Oktaputrining; Susandi C.; Suroso Suroso (PSIKODIMENSIA, 2017)
The aim of this research to prove empirically whether there is (1) the relationship of social support and marital satisfaction with post partum blues, (2) social support with post partum blues, (3) marital satisfaction with post partum blues. The subjects of this study were women aged 18-35 years and newly gave birth to the first child in healthy condition in the district of Madiun with the age of 3-14 days old baby which amounted to 35 primiparous moms. Data collection for postpartum blues tendencies, social support, and marital satisfaction in primiparous moms using the EPDS (Edinburgh Postnatal Depression Scale) scale, the scale of social support and the third marriage satisfaction scale of this scale have been tested for its validity and reliability. Sampling technique in this research with saturated sampling technique. Data analysis method was done by using multiple regression analysis technique which resulted from data analysis known (1) there is relationship between social support and marriage satisfaction with post partum blues, F = 9,319; (p) = 0,001 (p 0,05) (3) there is negative relation between marriage satisfaction with post partum blues, t = -2.755 (p) = 0.010 (p